Glutamate dynamics in the dorsolateral striatum of rats with goal-directed and habitual cocaine-seeking behavior - Giangrasso, Danielle M.; Veros, Kaliana M.; Timm, Maureen M.; West, Peter J.; Wilcox, Karen S.; Keefe, Kristen A. (Frontiers in Molecular Neuroscience, 2023)
The shift from drug abuse to addiction is considered to arise from the transition between goal-directed and habitual control over drug behavior. Habitual responding for appetitive and skill-based behaviors is mediated by potentiated glutamate signaling in the dorsolateral striatum (DLS), but the state of the DLS glutamate system in the context of habitual drug-behavior remains undefined. Evidence from the nucleus accumbens of cocaine-experienced rats suggests that decreased transporter-mediated glutamate clearance and enhanced synaptic glutamate release contribute to the potentiated glutamate signaling that underlies the enduring vulnerability to relapse. Preliminary evidence from the dorsal striatum of cocaine-experienced rats suggests that this region exhibits similar alterations to glutamate clearance and release, but it is not known whether these glutamate dynamics are associated with goal-directed or habitual control over cocaine-seeking behavior. Therefore, we trained rats to self-administer cocaine in a chained cocaine-seeking and -taking paradigm, which yielded goal-directed, intermediate, and habitual cocaine-seeking rats. We then assessed glutamate clearance and release dynamics in the DLS of these rats using two different methods: synaptic transporter current (STC) recordings of patch-clamped astrocytes and the intensity-based glutamate sensing fluorescent reporter (iGluSnFr). While we observed a decreased rate of glutamate clearance in STCs evoked with single-pulse stimulation in cocaine-experienced rats, we did not observe any cocaine-induced differences in glutamate clearance rates from STCs evoked with high frequency stimulation (HFS) or iGluSnFr responses evoked with either double-pulse stimulation or HFS. Furthermore, GLT-1 protein expression in the DLS was unchanged in cocaine-experienced rats, regardless of their mode of control over cocaine-seeking behavior. Lastly, there were no differences in metrics of glutamate release between cocaine-experienced rats and yoked-saline controls in either assay. Together, these results suggest that glutamate clearance and release dynamics in the DLS are largely unaltered by a history of cocaine self-administration on this established cocaine seeking-taking paradigm, regardless of whether the control over the cocaine seeking behavior was habitual or goal directed.